Konsep Pendidikan Kepemimpinan Berbasis Tradisi: Telaah Etnopedagogi pada Tembang Tradisional Gundul-Gundul Pacul - Kholid Irsani; Aman Aman; Saefur Rochmat (Universitas Negeri Padang, 2022)
Leadership education is one of the principles in the development of a nation. Various paradigms and theories of leadership have come from various backgrounds. This study focuses on examining the concept of tradition-based leadership education contained in the gundul-gundul pacul song. This study uses a qualitative research method with a literature approach to examine and integrate the concept of leadership contained in gundul-gundul pacul song with the concept of contemporary leadership education. This study found that song of gundul-gundul pacul has various concepts that are ideal to be applied in contemporary leadership ethnopedagogy because they have similarities in various factors such as communication, discipline knowledge, and problem solving.